Composite anatomical variations of the sciatic nerve in relation to the piriformis muscle observed in cadaveric studies - Kumar Yadav, Subodh; Yadav, Renu; Kumar Adhikari, Rakesh (Journal of Chitwan Medical College, 2026)
Introduction: The sciatic nerve, originating from the ventral rami of the lumbosacral plexus (L4–S4), has motor and sensory innervation to the lower limbs. Its course and division patterns exhibit considerable anatomical variability, particularly in relation to the piriformis muscle, with vital clinical significance, like piriformis syndrome and sciatica. This study aims to find out such variations via cadaveric dissection in the local population. Method: This descriptive observational study was performed on 50 lower limbs from 25 adult embalmed cadavers (15 male and 10 female) in the Department of Anatomy, Birat Medical College, Nepal, from 20 Sep to 30 Oct 2025. Ethical approval was obtained. Dissections of the gluteal and posterior thigh regions were carried out bilaterally to trace the sciatic nerve in relationship with the Piriformis muscle, photographed, and classified into six types according to Beaton and Anson’s classification system. Data were analysed descriptively for frequency and percentages. Result: Among the 50 sciatic nerves examined, Type A was most prevalent, observed in 36(72%). Type D and Type F patterns were identified in 6 specimens each (12% each). Additionally, a novel variation, not included in Beaton and Anson’s classification, was observed in 2 specimens (4%), where the Sural nerve arose directly from the sciatic nerve on both sides. Conclusion: The study highlights the high frequency of anatomical variability in the formation and division of the sciatic nerve within the gluteal region, which is vital for clinicians, surgeons, and anaesthesiologists to minimize iatrogenic complications during interventions.